Where Have All the IPOs Gone? - Gao, Xiaohui; Ritter, Jay R.; Zhu, Zhongyan (Journal of Financial and Quantitative Analysis, 2013)
Abstract During 1980–2000, an average of 310 companies per year went public in the United States. Since 2000, the average has been only 99 initial public offerings (IPOs) per year, with the drop especially precipitous among small firms. Many have blamed the Sarbanes-Oxley Act of 2002 and the 2003 Global Settlement’s effects on analyst coverage for the decline in IPO activity. We find very little support for the conventional wisdom, and we offer an alternative explanation. Our economies of scope hypothesis posits that the advantages of selling out to a larger organization, which can speed a product to market and realize economies of scope, have increased relative to the benefits of operating as an independent firm.